Domestic violence as a consequence of nusyuz under the Islamic law and legislation of Indonesia - Zuhdi, Syaifuddin; Kuswardani; Prakosa, Andria Luhur; Kurnianingsih, Marisa; Astuti, Widi; Ab Rahman, Rozanah (GIAP Journals, 2019)
Purpose of the study: This paper aims to clarify the views of Islamic law on the acts of domestic violence as a consequence of nusyuz (disobedience) and its position under the legislation of Indonesia. Methodology: This research was conducted by using the library research method. Documentary techniques are used in data collection, primary data is obtained from books, journals, and writings that directly discuss the material or problem under study, and from the secondary literature, which implicitly discusses it and is still quite relevant to be a comparison. Main Findings: The findings of this discussion revealed that the legislation of Indonesia is very protective of women, which is in line with the Islamic law principle that prioritizes persuasive and not repressive efforts in overcoming conflicts in the household. The compilation of Islamic law does not regulate the beating of wife, but the rule contained in Law No. 23 of 2004 on the elimination of domestic violence prohibits violence in the household. Applications of this study: This study can be useful for Indonesian people, especially for women and human right activists. Novelty/Originality of this study: The novelty in this discussion is the enlightenment of the public about the existence of a relationship between Islamic law and applicable law in Indonesia, wherein Islamic law is often not considered to be in harmony with the law in existing discussions.